Perceptions, Contagion, and Civil Unrest - Abi-Nassif, Christophe (World Bank, Washington, DC, 2020)
This paper investigates the empirical relationship between citizens' perceptions of economic and political conditions and the incidence of nonviolent uprisings. Perceptions are measured by aggregating individual-level data from regional barometer surveys. The main results show that negative perceptions of political conditions -- proxied by the share of the population that is generally dissatisfied with the way democracy works -- have a significant positive effect on the number of protests and strikes. Negative perceptions of economic conditions do not seem to be significantly related to the latter. This generally holds across a large sample of countries and is particularly the case for Western and Central European countries as well as high-income countries. In developing economies, however, social protests appear to be driven by dissatisfaction with economic and political conditions. The heterogeneous effects of perceptions on uprisings across geography and income groups, however, are not robust and susceptible to changes in estimators and model specification. In particular, the international contagion of protests eliminates this international heterogeneity, implying that the incidence of uprisings in nearby countries tends to generate protests at home through its effect on perceptions related to political conditions in high-income countries. Overall, the effect of perceptions about political conditions, along with protest contagion, is robust to the inclusion of numerous control variables that capture actual economic conditions and the quality of governance across countries. The results are also robust to the use of seemingly valid instrumental variables, alternative count-data estimators, and sample composition.